2024
DOI: 10.3390/su16093866
|View full text |Cite
|
Sign up to set email alerts
|

Which Values Matter Most to Romanian Consumers? Exploring the Impact of Green Attitudes and Communication on Buying Behavior

Răzvan-Andrei Corboș,
Ovidiu-Iulian Bunea,
Monica Triculescu
et al.

Abstract: The increasing commitment to sustainable consumption has intensified the scholarly focus on the determinants of environmentally friendly consumer behavior. This investigation provides an insight into the intricate interplay between green consumer values, functional (FV), conditional (CV), social (SV), and emotional (EV), and their impact on buying behavior (BB). Using survey data, we scrutinized the mediating roles of attitudes toward purchasing green products (APGP) and receptivity to green communication (RGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Likewise, it has been shown that perceived emotional value influences the purchase intention of healthy products; this finding is supported by researchers Sánchez et al [84] and Bonisoli and Micolta [85] who place special emphasis on specifying that emotional value is part of a set of evaluative aspects that have a positive influence on the consumer's purchase intention; furthermore, another recent study has shown that the interaction between emotional value and purchase intention of healthy products is explained by consumer perception; that is, when they feel an important attachment between themselves and the brand and/or product, they will not hesitate to choose it [86]. In this way, emotional value assumes a leading role where the connection between the consumer and the product is lasting, thus generating greater willingness to purchase when choosing a product, which generates an important advantage for the brand over the competition since the barrier of the purchase modality is not a limitation when the emotional value exists [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it has been shown that perceived emotional value influences the purchase intention of healthy products; this finding is supported by researchers Sánchez et al [84] and Bonisoli and Micolta [85] who place special emphasis on specifying that emotional value is part of a set of evaluative aspects that have a positive influence on the consumer's purchase intention; furthermore, another recent study has shown that the interaction between emotional value and purchase intention of healthy products is explained by consumer perception; that is, when they feel an important attachment between themselves and the brand and/or product, they will not hesitate to choose it [86]. In this way, emotional value assumes a leading role where the connection between the consumer and the product is lasting, thus generating greater willingness to purchase when choosing a product, which generates an important advantage for the brand over the competition since the barrier of the purchase modality is not a limitation when the emotional value exists [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, purchase attitude is used to represent the overall evaluation of the consumer's behavior to buy green products. The attitude of consumers toward green products can affect their decisions regarding green consumption [28], and consumption attitude can significantly positively affect consumption behavior [29]. Consumers with positive attitudes consider that green consumption can improve the existing environment, meet their spiritual needs, and stimulate their willingness to buy green products [30].…”
Section: Attitudes Toward Green Purchasesmentioning
confidence: 99%